Implementasi Perhitungan Harga Pokok Produksi (HPP) dalam Meningkatkan Profitabilitas pada UMKM Rasa Dewa - Sheva Nashwa Kamila; Callysta Athifa Pribadi; Aditya Mahardika Hidayat; Siti Fadhilah Nurfaizah; Muhammad Abiyyu Dzakwan Tirta; Farida Ratna Dewi; Sari Heviawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyse and implement the calculation of Cost of Goods Sold (COGS) using the full costing method at UMKM Rasa Dewa to increase profitability and help set more realistic and competitive selling prices. This study uses a mixed approach, namely qualitative and quantitative methods. The results of the study indicate that the calculation of COGS using the full costing method provides higher results than the simple method previously used by UMKM. The difference in production costs found was IDR 1,402,371 for starfruit juice products and IDR 2,881,150 for starfruit syrup products. This is due to the use of the full costing method which includes all cost elements, both direct and indirect costs such as depreciation of equipment, transportation, and other overhead costs that were not previously calculated. Meanwhile, the initial calculation of UMKM Rasa Dewa only included basic costs such as raw materials, direct labor, and packaging materials. By implementing the full costing method, UMKM can obtain a more accurate and comprehensive picture of production costs. This provides a more appropriate basis for consideration in setting product selling prices to increase profitability sustainably.